2016
DOI: 10.1016/j.neuron.2016.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Divergent Routing of Positive and Negative Information from the Amygdala during Memory Retrieval

Abstract: SUMMARY Although the basolateral amygdala (BLA) is known to play a critical role in the formation of memories of both positive and negative valence, the coding and routing of valence-related information is poorly understood. Here, we recorded BLA neurons during the retrieval of associative memories and used optogenetic-mediated phototagging to identify populations of neurons that synapse in the nucleus accumbens (NAc), the central amygdala (CeA) or ventral hippocampus (vHPC). We found that despite heterogeneou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

33
339
2
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 358 publications
(401 citation statements)
references
References 43 publications
33
339
2
3
Order By: Relevance
“…Retro-Cre-GFP was packaged in AAV serotype 6 which exhibits efficient retrograde transport via mechanisms that are likely dependent on dynein and kinesin-2 proteins (Murlidharan et al, 2014;Rothermel et al, 2013;Salegio et al, 2013). Similar studies have used recombinant canine adenovirus 2 (CAV2) or AAV serotype 5 to manipulate neural circuits (Beyeler et al, 2016;Marchant et al, 2015). Most commonly, studies have utilized methodology that involves optogenetic inhibition at the virus infusion site (to target discrete brain nuclei) or at the terminal region of the target circuit following virus injection at the cell body region, even though these approaches are more prone to affect fibers of passage (Beyeler et al, 2016;Stamatakis and Stuber, 2012).…”
Section: Combinatorial Viral Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…Retro-Cre-GFP was packaged in AAV serotype 6 which exhibits efficient retrograde transport via mechanisms that are likely dependent on dynein and kinesin-2 proteins (Murlidharan et al, 2014;Rothermel et al, 2013;Salegio et al, 2013). Similar studies have used recombinant canine adenovirus 2 (CAV2) or AAV serotype 5 to manipulate neural circuits (Beyeler et al, 2016;Marchant et al, 2015). Most commonly, studies have utilized methodology that involves optogenetic inhibition at the virus infusion site (to target discrete brain nuclei) or at the terminal region of the target circuit following virus injection at the cell body region, even though these approaches are more prone to affect fibers of passage (Beyeler et al, 2016;Stamatakis and Stuber, 2012).…”
Section: Combinatorial Viral Approachmentioning
confidence: 99%
“…Similar studies have used recombinant canine adenovirus 2 (CAV2) or AAV serotype 5 to manipulate neural circuits (Beyeler et al, 2016;Marchant et al, 2015). Most commonly, studies have utilized methodology that involves optogenetic inhibition at the virus infusion site (to target discrete brain nuclei) or at the terminal region of the target circuit following virus injection at the cell body region, even though these approaches are more prone to affect fibers of passage (Beyeler et al, 2016;Stamatakis and Stuber, 2012). In particular, the combinatorial viral approach is essential (a) to manipulate proteins that are not expressed at the terminal region of target circuits and (b) to mitigate the current scarcity of Cre-driver lines and unavailability of Cre-dependent opsins packaged in retrogradely transported viruses (Saunders et al, 2015;Witten et al, 2011;Warden et al, 2014).…”
Section: Combinatorial Viral Approachmentioning
confidence: 99%
“…However, it is also interesting to observe differential effect of valence (positive versus negative) in future studies (cf., Beyeler et al, 2016;Bradley et al, 1992).…”
Section: Memory Enhancement By Emotional Contextmentioning
confidence: 99%
“…We have begun to unravel how BLA populations encode valence in physiological conditions (6)(7)(8). We can now start to investigate how valence circuits are dysfunctional in pathologies such as anxiety and depression.…”
Section: Parsing Reward From Aversionmentioning
confidence: 99%
“…During this time, my collaborators and I assessed different subpopulations of the BLA that relay integrated information to distinct regions. Over multiple studies, I identified circuit, synaptic, and molecular mechanisms by which three distinct neural populations in the BLA encode innate and learned behaviors (6)(7)(8).…”
mentioning
confidence: 99%